Study on Evaluation of the Efficacy of Different Fungicides against Fusarium musae, a Fruit Rot Disease of Banana - Tushar T. Baria (New Visions in Biological Science Vol. 4, 2021)
Very meagre research work has been done on fusarium fruit rot diseases of banana and their management in India, therefore to extend the shelf life of banana fruits and to reduce the losses caused by post-harvest diseases; it is felt worthwhile to carry out the investigations on fusarium fruit rot diseases of banana and its management under south Gujarat condition. Therefore, the present investigation was undertaken. In the present study, nine fungicides were evaluated against F. musae using poison food technique on PDA medium at different concentrations among them mancozeb 75 WP at 2500ppm, azoxystrobin (20%) + difenoconazole (12.5%) at 1000ppm and propiconazole (25 EC) at 500ppm and 1000ppm were found to be the utmost superior because of cent per cent inhibition of mycelial growth of F. musae under in vitro. Whereas, in vivo evaluation lowest fusarium fruit rot severity was observed with propiconazole (25 EC) at 1000ppm in pre (6.61%) and post- inoculation (6.7%) treatments at 8 days after inoculation. While azoxystrobin (20%) + difenoconazole (12.5%) at 500ppm and chlorothalonil (75 WP) at 2500ppm were found least effective in controlling the fusarium fruit rot severity in pre and post inoculation treatments at 8 days after inoculation.